The unfairness we feel: How positive and aggressive affect could shape relative deprivation and aggression - Yara J. Kassab; Georg Halbeisen; Eva Walther (BMC Psychology)
Abstract Background Relative deprivation (RD), the belief of being unfairly disadvantaged compared to a standard, has frequently been linked to aggressive behaviors. This study explored how affective experiences are associated with the perception of unfairness (i.e., RD) and, thus, influence aggressive behavior indirectly. Methods N = 184 participants were randomly assigned to one of two conditions of a game task, in which they experienced either deprivation or no deprivation as the difference between own rewards and the rewards of a fictitious other player. We assessed the subjective perception of RD and affective experiences attributed to the game before measuring aggressive behavior towards the other player in a point subtraction task. Results Sequential mediation analysis suggested that increases in aggressive affect and decreases in positive affect could be linked to perceiving the game as more unfair for deprived participants, which in turn increased rates of aggressive behavior. Conclusions Adding to the existing literature, these findings suggest that RD could not only lead to aggression through an affective route but that affective experiences potentially alter perceptions of RD and thus aggressive behavior indirectly.